Lady Chapel - Ghosh, Ayan (2023)
The Lady Chapel (seen here) is a traditional British term for a chapel dedicated to "Our Lady", Mother Mary. The chapel has some notable memorials, including Daniel Seton, Lieutenant-Governor of Surat Castle (top left), and Katherine Kirkpatrick (top right), mother to James Achilles Kirkpatrick, who served as Company Resident at Hyderabad (Deccan).